Cerium‐Based M4L4 Tetrahedra as Molecular Flasks for Selective Reaction Prompting and Luminescent Reaction Tracing. Issue 8 (21st January 2014) - Jiao, Yang; Wang, Jian; Wu, Pengyan; Zhao, Liang; He, Cheng; Zhang, Jing; Duan, Chunying
Abstract The application of metal–organic polyhedra as "molecular flasks" has precipitated a surge of interest in the reactivity and property of molecules within well‐defined spaces. Inspired by the structures of the natural enzymatic pockets, three metal–organic neutral molecular tetrahedral, Ce‐TTS, Ce‐TNS and Ce‐TBS (H6TTS: N′, N′′, N′′′‐nitrilotris‐4, 4′, 4′′‐(2‐hydroxybenzylidene)‐benzohydrazide; H6TNS: N′, N′′, N′′′‐nitrilotris‐6, 6′, 6′′‐(2‐hydroxybenzylidene)‐2‐naphthohydrazide; H6TBS: 1, 3, 5‐ phenyltris ‐4, 4′, 4′′‐(2‐hydroxybenzylidene)benzohydrazide), which exhibit different size of the edges and cavities, were achieved through self‐assembly by incorporating robust amide‐containing tridentate chelating sites into the fragments of the ligands. They acted as molecular flasks to prompt the cyanosilylation of aldehydes with excellent selectivity towards the substrates size. The amide groups worked as trigger sites and catalytic driven forces to achieve efficient guest interactions, enforcing the substrates proximity within the cavity. Experiments on catalysts with the different cavity radii and substrates with the different molecular size demonstrated that the catalytic performance exhibited enzymatical catalytic mechanism and occurred in the molecular flask. These amides were also able to amplify guest‐bonding events into the measurable outputs for the detection of concentration variations of the substrates, providing the possibility for metal–organic hosts to work as smart molecular flasks for the luminescent tracing of catalytic reactions.